Study of ECG changes in patients with acute stroke: a hospital based cross sectional study - V., Rambabu M.; P., Viswajyothi Rao (International Journal of Advances in Medicine, 2018)
Background: Physicians are confronted on having ECG in patients with acute stroke as it can mimic that of myocardial infarction/ischemia. They should be aware of these changes taking place in patients with acute stroke and not due to myocardial infarction/ischemia. The objective of the present study was to study ECG changes in patients with acute stroke. Methods: A hospital based cross sectional study was carried out for a period of six months at Malla Reddy Hospital. A total of 100 patients were included who were eligible for the presents study as per the inclusion and exclusion criteria. Detailed clinical examination, history, lipid profile, blood pressure, BMI, addictions, RBS and ECG were done for all selected patients. Data was analysed using means, proportions. Statistical tests like chi square test and t test were used. Results: Majority of patients with acute stroke were above 60 years of age, males, urban residents, professional and skilled persons, and alcoholics. Based on the study of ECG among patients with acute stroke it was found that T wave inversion was the most common ECG change found in 33% and this was more in females (36.1%) compared to 31.3% in males. LVH was next common condition found on ECG of acute stroke patients but this time its incidence was more in males (25%) compared to females with only 13.9%. Factors like age, BMI, SBP, DBP, TC, TG, LDL, VLDL, HDL, addictions, residence, sex, family history were not found to be associated with ECG changes. Conclusions: T wave inversion and left axis deviation along with left ventricular hypertrophy were common ECG changes in patients with acute stroke. No studied factor was found to be associated with ECG changes in patients with acute stroke.